Village Fund Management System Against Financial Reports and Revenue Budgets in Rowolaku - Sa'adah, Naelu; Adinugraha, Hendri Hermawan (MUAMALATUNA, 2022)
The Village Fund is a number of budgets received by the village every year originating from taxes, APBN, and Regency/City APBDes which are used to fund village development activities. This study aims to determine the meaning of village funds, how village funds are managed by the village government, how the financial accounting system for managing village funds is, and how the influence of the village fund management system on village financial reports. The research method used is qualitative research by conducting interviews and observations. The village fund management system will affect village financial reports. If there was a transaction that issued or received new cash, it would be recorded. Then with the development of technology, the accounting record system has changed from a manual basis to an accrual basic. From this change, the staff experienced difficulties due to the education level of the staff employees who only reached SMA/SMK equivalent which at the time they received minimal education in accounting learning. In this case, the village fund management system in Rowolaku Village, Pekalongan Regency has undergone a change, namely from a manual system to a computerized system where from these changes it is hoped that these problems can be resolved properly.